PERAN PENGELOLAAN ARSIP DALAM MENINGKATKAN MUTU PELAYANAN RUMAH SAKIT KOTA MATARAM - Nurul Haminiah; Muhammad Aditya Rachman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
Effective archive management is the backbone of hospital administration, directly impacting the speed and accuracy of medical services. This article aims to analyze how archive management, both physical and digital (e-archive), contributes to improving the quality of services in hospitals in Mataram City. Through a literature review, it was found that the integration of a standardized archiving system can reduce patient waiting times, minimize medical errors due to inaccurate data, and support appropriate clinical decision-making. The study results indicate that archive digitization is a crucial solution to address the challenges of the ever-increasing volume of patient data in urban healthcare facilities such as Mataram. Furthermore, the study emphasizes that the successful implementation of archive management is highly dependent on the readiness of human resources and the support of adequate information technology infrastructure. Optimizing electronic medical records has been proven to significantly minimize the risk of document loss and data input errors that often occur in manual systems. This study concludes that the transformation of archive management from a conventional to a digital system is a strategic step that not only improves operational efficiency but also strengthens the legal aspects and protection of patient data. Thus, strengthening archives management is a vital instrument in realizing good hospital governance and ensuring the sustainability of patient safety-oriented healthcare services in Mataram City.